Hepatotoxicity effect of alcoholic beverages on histology and IL-6 gene detection in Rattus norvegicus using polymerase chain reaction - Fitria Diniah Janah Sayekti; Vector Stephen Dewangga; Muhammad Taufiq Qurrohman (Intelektual Pustaka Media Utama, 2026)
The liver is an organ that has an important role in metabolic and detoxification processes. Alcohol consumption will cause metabolic disorders in the liver and can cause changes in histological structures. Interleukin-6 has a profound role in liver pathology and plays an important role in the body's defense mechanism, and contributes to the manifestation of tissue damage. This study was an experimental study using 20 Rattus norvegicus treated with 25% alcohol, and a normal treatment only given distilled water. Histological observations were carried out on each preparation in 5 fields of view. The hepatotoxicity effect of alcohol was observed based on the presence of cell degeneration and necrosis in histological preparations stained with hematoxylin eosin. IL-6 detection with polymerase chain reaction was analyzed qualitatively using electrophoresis. Based on the statistical test results, the sig. (2 tailed) of 0.00 < 0.05 so that it can be seen that there is a significant difference in histological results between the normal control group without treatment and the group induced by alcohol. The administration of alcoholic beverages with 25% ethanol content in vivo for 21 days causes necrosis and bleeding around the hepatocyte cells. IL-6 overview appeared to be stronger in the group with alcohol-induced drinking, it could indicate that giving alcohol causes a higher inflammatory response. This study provides scientific evidence that alcohol consumption significantly damages the liver. Further research can be conducted to increase the sample size and quantitatively assess IL-6 expression.